Morris the Moose - Wiseman, Bernard (New York : Harper & Row, 1989)
Determined to prove that the cow he meets is really a moose, Morris the moose enlists the help of a rather confused deer and horse.
330L
Decoding demand: 46 (medium)
Semantic demand: 24 (low)
Syntactic demand: 43 (medium)
Structure demand: 59 (medium)
Accelerated Reader AR
Keywords: Moose; Fiction; Animals; Fiction; Humorous stories; Early chapter